Rancang Bangun Sistem Informasi Helpdesk Ticketing Berbasis Web pada SDN Babakan 01 Menggunakan Metode Waterfall - Yulianti Yulianti; Ahmad Firmansyah; Muhammad Noval Nur Auliya; Muhammad Arinal Haq; Andini Afaf; Irpan Kusyadi (Teknik Informatika Universitas Pamulang, 2022)
In an activity in the education unit, the Helpdesk Ticketing System can be an information technology facility to improve service quality. At SDN Babakan 01 the complaint process for information technology problems does not use a system, so IT operators who receive incident reports, come and confirm the problem directly, this creates a problem, namely in the complaint report documentation process it is not recorded properly and quickly. In designing information technology Helpdesk Ticketing System at SDN Babakan 01, the authors conducted interviews and observations first before designing a website-based Helpdesk Ticketing System where the model used was SDLC (Software Development Life Cycle) and the method used was the Waterfall method, so that the system designed can be used by SDN Babakan 01 operators to accommodate and organize any problem reports properly, so that reports can be structured properly, minimize communication errors with IT operators, and can present report data quickly.